From multi-parametric programming theory to MPC-on-a-chip multi-scale systems applications - Pistikopoulos, Efstratios N. (Computers & chemical engineering, 2012)
An overview of multi-parametric programming and control is presented with emphasis on historical milestones, novel developments in the theory of multi-parametric programming and explicit MPC as well as their application to the design of advanced controller for complex multi-scale systems.